2019
DOI: 10.1016/j.apgeog.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the spatial decision making of terrorists: The discrete choice approach

Abstract: This is the first study to apply a discrete choice model to understand terrorist spatial decision making. The findings support the proposition that terrorists make decisions that are guided by rationality and act in a similar way to urban criminals. A conditional logistic regression ascertained which characteristics increased the likelihood that an area would be selected as a target, using a dataset of attacks carried out by the Provisional Irish Republican Army in Belfast over a twentyyear period. An increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Finally, it is important to investigate distance to target (i.e., the nearness element) as criminologists have done in the terrorism context. Drawing on the discrete choice spatial modeling approach (Bernasco & Nieuwbeerta, ), Marchment and Gill () measured the Euclidean distance between the offender's home and target area, finding that the Provisional Irish Republican Army (PIRA) was less likely to choose attack areas located farther away. It may also be useful to expand nearness to include the attacker's personal “familiarity” with the setting as an indicator of his or her “awareness space” (Brantingham & Brantingham, ).…”
Section: Scp Terrorism and Preventing Or Reducing Public Mass Violencementioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is important to investigate distance to target (i.e., the nearness element) as criminologists have done in the terrorism context. Drawing on the discrete choice spatial modeling approach (Bernasco & Nieuwbeerta, ), Marchment and Gill () measured the Euclidean distance between the offender's home and target area, finding that the Provisional Irish Republican Army (PIRA) was less likely to choose attack areas located farther away. It may also be useful to expand nearness to include the attacker's personal “familiarity” with the setting as an indicator of his or her “awareness space” (Brantingham & Brantingham, ).…”
Section: Scp Terrorism and Preventing Or Reducing Public Mass Violencementioning
confidence: 99%
“…Other factors to consider are natural barriers that may impede travel, such as major bodies of water or woodlands, as well as the ease of accessibility to and from the targeted site via major highways, streets, sidewalks, railways, or other thoroughfare's and routes (see earlier discussion; Brantingham & Brantingham, ; Johnson & Bowers, ; Johnson & Summers, ; Marchment & Gill, ). Lastly, an understudied aspect of the near dimension is the method of transport offenders use to reach the target location.…”
Section: Scp Terrorism and Preventing Or Reducing Public Mass Violencementioning
confidence: 99%
See 1 more Smart Citation
“…International classifications of terrorist targets, by including the ones of the European Commission definitions, recognize "hard" and "soft" targets in relation to the protection strategies and risk management that are applied to them [10,13,18,19]. Government buildings, military institutions and additional strategic buildings are "hard targets", characterized by codified and significant control levels (including restricted access to the public) and protection (including armed guards) measures [18,20]. On the contrary, urban BEs (including open spaces) are ideally "soft targets" for terrorist acts, being characterized by a "high concentration of people, low or no security against violent attacks and attraction for the attacker" due to the exposure contents [19].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that lethal terrorist attacks tend to generate more deaths in ethnically polarized areas and in locations within democratic countries. Another study by Marchment and Gill [19] applied a discrete choice model to understand terrorist spatial decision making. These authors concluded that terrorists are similar to traditional criminals in their decision making, in addition to being influenced by spatial context, such as the distance from their home location to the attack location, or the presence of a premise relevant to their ideology.…”
Section: Introductionmentioning
confidence: 99%